PERLUNYA MANUSIA TERHADAP AGAMA: PERSPEKTIF METODOLOGI STUDI ISLAM - Zuhair Abdurrahman; Rendy Fauzi; Maftuh Ajma’in (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze the essence of human beings as Homo Religiosus from a multidisciplinary perspective encompassing philosophical, psychological, sociological, and theological dimensions. The main focus is to demonstrate that religiosity is not merely an additional attribute but an integral part of human consciousness that drives the search for meaning and connection with transcendent reality. This research employs a qualitative method through a literature review of key thinkers such as Mircea Eliade, Rudolf Otto, and Viktor Frankl. The findings indicate that from a psychological perspective, religion functions as a mechanism for fulfilling the human need for meaning and alleviating existential anxiety, while from a sociological perspective, it serves as a foundation for moral values and social integration. Furthermore, modernity presents challenges in the form of spiritual crises and loss of meaning, which require a comprehensive methodological approach to understand religious phenomena. Therefore, integrating normative and historical approaches is essential to ensure that religious teachings remain relevant in addressing the dynamics of modern life without losing their spiritual essence.